2008
DOI: 10.1002/mrm.21441
|View full text |Cite
|
Sign up to set email alerts
|

Numerical field evaluation of healthcare workers when bending towards high‐field MRI magnets

Abstract: In MRI, healthcare workers may be exposed to strong static and dynamic magnetic fields outside of the imager. Body motion through the strong, non-uniform static magnetic field generated by the main superconducting magnet and exposure to gradient-pulsed magnetic fields can result in the induction of electric fields and current densities in the tissue. The interaction of these fields and occupational workers has attracted an increasing awareness. To protect occupational workers from overexposure, the member stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
(34 reference statements)
0
14
0
Order By: Relevance
“…Some studies have quantified the magnetic field experienced by the operators experimentally (11), and the risk related to the exposure has been analyzed statistically (12). Because in vivo measurements of induced quantities are unfeasible, most of the studies aimed at quantifying motion-induced fields rely on computations (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). However, none of these studies included the computation of the exposure indexes recently recommended by ICNIRP, which could become a legal requirement in the next future.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have quantified the magnetic field experienced by the operators experimentally (11), and the risk related to the exposure has been analyzed statistically (12). Because in vivo measurements of induced quantities are unfeasible, most of the studies aimed at quantifying motion-induced fields rely on computations (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). However, none of these studies included the computation of the exposure indexes recently recommended by ICNIRP, which could become a legal requirement in the next future.…”
Section: Introductionmentioning
confidence: 99%
“…The 5-mm resolution HUGO model is adopted for this study [6]. In this particular scenario, the body model was facing the MRI entrance and was placed a certain distance away from the device end so that there would be a 10-mm gap between the head and the device end at the bend angle of 90 degrees.…”
Section: Implementation and Resultsmentioning
confidence: 99%
“…For example, near the entry to the bore of a 3T MRI where j$B o j tends to be greatest, it can be shown that current densities over 0.1 A/m 2 may be produced in conductive tissues due to the voltage induced by normal movement. 38,39 This is more than twice the 0.04 A/m 2 (low frequency) limit for exposure of workers recommended by the International Commission for Non-Ionizing Radiation Protection (ICNIRP). 40 Whether or not one considers the ICNIRP limit as overly conservative, currents induced in tissue deserve serious attention as a potential MRI safety concern, especially as new high-field MRI systems are introduced.…”
Section: Direct Interactions Between the Static Magnetic Field And LImentioning
confidence: 94%
“…It is well known that movement in a magnetic field can induce a voltage (due to Faraday's law of induction, discussed in more detail later) in electrically conductive materials, including biological tissues, especially when the motion is through regions of space where the magnetic field changes steeply. For example, near the entry to the bore of a 3T MRI where |Bo| tends to be greatest, it can be shown that current densities over 0.1 A/m may be produced in conductive tissues due to the voltage induced by normal movement . This is more than twice the 0.04 A/m (low frequency) limit for exposure of workers recommended by the International Commission for Non‐Ionizing Radiation Protection (ICNIRP) .…”
Section: The Static Magnetic Fieldmentioning
confidence: 99%